The dermatology life quality index (DLQI) and the hospital anxiety and depression (HADS) in Chinese rosacea patients. Issue 4 (21st April 2018) - Wu, Yanyu; Fu, Chaowei; Zhang, Wei; Li, Caixia; Zhang, Jie
Abstract: The study aims to investigate the quality of life (QOL) and the psychological situation in Chinese patients with rosacea. A total of 196 healthy controls and 201 rosacea patients were involved in the final analysis. The general information, the Dermatology Life Quality Index (DLQI) and the Hospital Anxiety and Depression Scale (HADS) were collected. Significantly higher DLQI, anxiety and depression score were observed in the rosacea group compared to the control group ( p  < .01). Total DLQI score of patients was positively related with anxiety ( r  = .526, p  < .001) and depression scores ( r  = .399, p  < .001) in HADS. Rosacea had significant psychological impact on Chinese patients and had substantial influence on their QOL. Physicians should address the psychosocial needs of rosacea patients as much as its physical symptoms.